2012
DOI: 10.2495/si120241
|View full text |Cite
|
Sign up to set email alerts
|

Determination of water requirement and irrigation timing forAmaranthus hybridusin Maiduguri metropolis, north-eastern Nigeria

Abstract: Crop water requirements and irrigation timing are particularly important in arid and semi-arid regions where water is scarce. In this paper, theoretical crop water requirements and irrigation timing for Amaranthus hybridus in Maiduguri metropolis, north-eastern Nigeria were determined under drip irrigation for the dry season. Reference evapotranspiration (ETo) was based on the PenmanMontieth formula and CROPWAT 8.0. An elemental irrigated area (A i ), crop canopy factor (Cp) and emitter application rates (ar) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The crop water requirement for the Amaranthus hybridus was determined using the climatic data in the study area for the Penman Monteith equation and the CROPWAT model as shown by Arku et al [21]. The mean crop water required for the designed drip irrigation system layout ( fig.…”
Section: Crop Water Requirement and Drip Irrigation Systemmentioning
confidence: 99%
“…The crop water requirement for the Amaranthus hybridus was determined using the climatic data in the study area for the Penman Monteith equation and the CROPWAT model as shown by Arku et al [21]. The mean crop water required for the designed drip irrigation system layout ( fig.…”
Section: Crop Water Requirement and Drip Irrigation Systemmentioning
confidence: 99%